Given:
The arithmetic sequence is −15, −33, −51, −69.
To find:
The nth term of the arithmetic sequence.
Solution:
We have,
−15, −33, −51, −69
Here,
First term: a = -15
Common difference is
![d = -33-(-15)](https://tex.z-dn.net/?f=d%20%3D%20-33-%28-15%29)
![d = -33+15](https://tex.z-dn.net/?f=d%20%3D%20-33%2B15)
![d = -18](https://tex.z-dn.net/?f=d%20%3D%20-18)
Now, nth term of an arithmetic sequence is
![a_n=a+(n-1)d](https://tex.z-dn.net/?f=a_n%3Da%2B%28n-1%29d)
Substitute a=-15 and d=-18.
![a_n=-15+(n-1)(-18)](https://tex.z-dn.net/?f=a_n%3D-15%2B%28n-1%29%28-18%29)
![a_n=-15-18n+18](https://tex.z-dn.net/?f=a_n%3D-15-18n%2B18)
![a_n=-18n+3](https://tex.z-dn.net/?f=a_n%3D-18n%2B3)
Therefore, the nth term of the given arithmetic sequence is
.
Answer:
5/36
Step-by-step explanation:
I added them up
Tell me if I am wrong.
Can I get brainliest
Answer: ![\large\boxed{\text{No Solution}}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%5Ctext%7BNo%20Solution%7D%7D)
Step-by-step explanation:
<u>Given equation</u>
![\sqrt{t+1}+9=7](https://tex.z-dn.net/?f=%5Csqrt%7Bt%2B1%7D%2B9%3D7)
<u>Subtract 9 on both sides</u>
![\sqrt{t+1}+9-9=7-9](https://tex.z-dn.net/?f=%5Csqrt%7Bt%2B1%7D%2B9-9%3D7-9)
![\sqrt{t+1}=-2](https://tex.z-dn.net/?f=%5Csqrt%7Bt%2B1%7D%3D-2)
<u>Conclusion</u>
![\text{Since radical values are always positive, it is false that }\sqrt{t+1}\text{ will equal to -2}](https://tex.z-dn.net/?f=%5Ctext%7BSince%20radical%20values%20are%20always%20positive%2C%20it%20is%20false%20that%20%7D%5Csqrt%7Bt%2B1%7D%5Ctext%7B%20will%20equal%20to%20-2%7D)
![\text{Therefore, it is }{\large\boxed{\text{No Solution}}}\text{ in the context of real numbers}](https://tex.z-dn.net/?f=%5Ctext%7BTherefore%2C%20it%20is%20%7D%7B%5Clarge%5Cboxed%7B%5Ctext%7BNo%20Solution%7D%7D%7D%5Ctext%7B%20in%20the%20context%20of%20real%20numbers%7D)
Hope this helps!! :)
Please let me know if you have any questions